Respuesta :

So you multiply -8 by 4 and get -32. So you have -32= 13u --7 over -8 multiplied by -8. The fractions would cancel out and leave you with -32= -3u +7 (because a negative plus a negative equals a positive). So then you subtract 7 from both sides and get -39= -3u. You then divide -3 on both sides and you get u=13.

[tex]\bf (-8)4=\cfrac{-3u-(-7)}{-8}(-8)\implies (-8)4=-3u-(-7)\cdot \cfrac{(-8)}{-8} \\\\\\ (-8)4=-3u-(-7)\cdot 1\implies -32=-3u+7\implies -39=-3u \\\\\\ \cfrac{-39}{-3}=u\implies \boxed{13=u}[/tex]